2011
DOI: 10.5897/ajb10.1236
|View full text |Cite
|
Sign up to set email alerts
|

Exploring storage protocols for yam (Dioscorea spp.) pollen genebanking

Abstract: Implementation of pollen genebanks allows the conservation of plant genetic resources at the haploid level, pollen genetic manipulations, scheduling of hybrid seed production and improvement of breeding efficiency. To establish pollen storage protocols for various genotypes of West African yams, laboratory experiments were conducted on fresh pollen and pollen stored under various conditions at the Genetic Resources Unit International Institute of Tropical Agriculture Ibadan, Nigeria (IITA). The storage treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Our study observed a 45% decrease in pollen germination from fresh pollens to one-year lyophilized pollens. Daniel et al, [44] also observed a sharp decrease in pollen germination of yam species after cryo-preservation. They recommended that wet-cold storage (hermetic cold storage without previous drying) is a superior method for long-term pollen viability compared to air-dried storage and freeze-drying.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Our study observed a 45% decrease in pollen germination from fresh pollens to one-year lyophilized pollens. Daniel et al, [44] also observed a sharp decrease in pollen germination of yam species after cryo-preservation. They recommended that wet-cold storage (hermetic cold storage without previous drying) is a superior method for long-term pollen viability compared to air-dried storage and freeze-drying.…”
Section: Discussionmentioning
confidence: 98%
“…However, the success rates vary according to the plant species. Many studies have reported in vitro germination of preserved pollens of yam using different techniques [20,23,24,[42][43][44]. For instance, Mondo et al, [20] achieved 26.4-59.7% in vitro germination in D. alata.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the success rates vary according to the plant species. Many studies have reported in vitro germination of preserved pollens of yam using different techniques [20,23,24,[42][43][44]. For instance, Mondo et al [20] achieved 26.4%-59.7% in vitro germination in D. alata.…”
Section: Discussionmentioning
confidence: 99%
“…Alexander et al [ 51 ] also claimed that Capsicum pollen could retain its viability and fertility for more than 42 months under cryopreservation. Pollen samples of yam retained their germination capacity even after 2 years when subjected to “wet-cold” conditions at −80 °C [ 52 ]. In cucurbits, pollen tube growth in watermelon was observed to be highest at 35 °C and lowest at 15 °C [ 53 ].…”
Section: Pollen Biology and Developmentmentioning
confidence: 99%